The Influence of the Probing–Prompting Learning Model Assisted by Couple Card Media on Students’ Learning Outcomes - Rahma, Natasya Alya; Amin, Lailla Hidayatul; Sholihah, Siti Fathiyatus (FONDATIA, 2025)
This study is motivated by the limited research on the integration of the Probing Prompting model with Couple Card media, despite the belief that dialogic approaches combined with concrete visual aids can enhance elementary students’ learning outcomes in thematic instruction. The study aims to analyze the implementation of the Probing Prompting model assisted by Couple Card media, describe students' learning outcomes, and assess the model’s effect on the learning achievement of Grade III students at MIN 4 Sukoharjo. A quantitative approach with a correlational design was employed, involving 108 students selected through total sampling. Data were collected using questionnaires to evaluate the implementation of the instructional model and final assessment (PAT) scores to measure learning outcomes. Data analysis was conducted using simple linear regression. The results indicate that the implementation of the Probing Prompting model with Couple Card media was at a high level, while student learning outcomes were categorized as good. Statistically, there is a positive and significant effect of the model’s implementation on students’ learning outcomes in thematic subjects, with a contribution of 8.3%. These findings suggest that combining structured questioning techniques with concrete visual media can enhance students’ cognitive engagement and academic performance. The study’s implications highlight the importance of developing interactive and contextual learning strategies at the elementary level and recommend further research to examine the model’s effectiveness across different educational stages and learning contexts.